Intrasubject relationship between striatal 18F-FP-CIT uptake and cardiac 123I-MIBG uptake differs by motor subtype in early Parkinson disease. Issue 33 (20th August 2021) - Jang, Wooyoung; Lee, Ji Young; Kim, Ji Young; Lee, Soo Jin; Kim, Tae Yoon; Choi, Yun Young; Kim, Hee-Tae; Kim, Chun K.
Abstract : Abstract: Parkinson disease (PD) is a heterogeneous neurodegenerative disorder. Dopamine transporter imaging using 123 I-2β-carbomethoxy-3β-(4-iodophenyl)- N -(3-fluoropropyl)-nortropane (FP-CIT) and noradrenergic cardiac imaging using 123 I-meta-iodobenzylguanidine (MIBG) have been used in combination or separately to study PD patients. Published results regarding uptake of the 2 tracers in each motor subtype are fairly abundant and mostly in agreement. However, data on the intrasubject association between dopaminergic and noradrenergic systems in PD patients are relatively scant and vary. We aimed to assess the intrasubject relationship between striatal dopamine transporter density using a PET tracer and cardiac sympathetic innervation in tremor-dominant subtype (TD) and akinetic-rigid subtype (AR) of PD. This study has a cross-sectional design. Thirty-one patients with early PD (17 TD/14 AR) who underwent both 123 I-MIBG cardiac scintigraphy and 18 F-FP-CIT PET/CT were retrospectively selected. We assessed the relationship between heart-to-mediastinum ratio (H/M) of 123 I-MIBG and specific (striatal)-to-nonspecific (cerebellar) dopamine transporter binding ratio (S/N) measured from 4 separate regions-of-interest (bilateral caudate nuclei and lentiform nuclei) of 18 F-FP-CIT in each motor subtype. S/N of all 4 striatal regions were significantly lower in the AR subgroup than in the TD subgroup. H/M was not significantly different. There was a significant intrasubject correlation between H/M and S/N of the lentiform nucleus in AR-PD but no correlation between H/M and any of 4 S/N in TD-PD. Our data suggest a coupled degeneration of nigrostriatal dopaminergic and myocardial sympathetic denervation in AR subtype, but not in TD subtype, of early PD patients. These different results between the 2 motor subtypes likely reflects the heterogeneous pathophysiology of PD.